PERBEDAAN MOTIVASI BELAJAR PKn YANG MENGGUNAKAN METODE SEMINAR SOCRATES DENGAN KONVENSIONAL DI SMPNEGERI 1 PANGKALAN LESUNG KABUPATEN PELALAWAN - Dewi Ratnawati Ratnawati; Zahirman '; Sri Erlinda Erlinda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study was motivated by the low motivation to learn civics student at SMPN 1 Base Dimples Pelalawan. The problem of pene; otian is: "is there a difference motivation to learn civics that using the conventional method socrates seminar at SMPN 1 Base Dimples Pelalawan?". This study aims to determine the difference motivation to learn civics students who use the conventional method socrates seminar in SMP Negeri 1 Base Dimples Pelalawan.Penelitian District was conducted in SMP Negeri 1 Base Dimples Pelalawan in January 2015. This study is a descriptive research into population kuantitatifyang in this research is class VIII SMP Negeri 1 Base Dimples Pelalawan. The sample in this study was based technique of "purposive sampling".Where take classes in the sample is VIII A (control group) students were given a lecture, and class VIII B (grade Experiment ) students were given a seminar Socratic method and then the data analysis using the homogeneity test and test "t". Research conducted found that there are differences in student motivation anatara Socratic seminars methods and conventional methods in SMP Negeri 1 Base Dimples Pelalawan (t = 8.8 > table = 1.67). Where there is an average increase motivation to learn civics class control of 23.25 into 24.96 and an average increase motivation to learn civics class experiment of 23.12 to 30.25. Thus the hypothesis which says there is a difference motivation to learn civics that using the conventional method socrates seminar at SMPN 1 Base Dimples acceptable Pelalawan Keywords: Motivation Learning, Socratic Seminar